How podcasting is changing the audio storytelling genre. (1st April 2016) - McHugh, Siobhán
This article explores the impact of the post-2014 podcast resurgence on non-fictional audio storytelling formats. The empirical study comprises themed commentary by five significant US, European and Australian editors who commission and produce audio documentaries and features for broadcast and/or podcast. The article provides insights into the changing role played by public broadcasters, the growth of independent podcast networks and the perceived differences between radio and podcasting as a mode of delivering and receiving audio content. Of particular significance is the belief of senior commissioning editors that podcasting is fomenting a new, more informal, genre of audio narrative feature centred on a strong relationship between host and listener, with content that is 'talkier' and less crafted. The US audio storytelling podcast sector is growing fast, and much of it has links to a public media ethos, but how to resource it without compromising its editorial independence remains unresolved.